Dissemination of Tracer Usage Using Microsoft Access in the Medical Record Unit at Air Dingin Health Center, Padang City: Tracer Usage Using Microsoft Access in the Medical Record - Deni Maisa Putra (APTIRMIKI, 2022)
The development of information technology today affects various aspects of life and profession, one of which is in the field of health services, especially in patient medical records. Health data and information contained in medical records are very useful for the management of health care institutions to assess whether their services are of high quality, efficient and effective. The speed in providing medical record files to the poly is one of the indicators of service quality in medical records, both in and out of medical records from Filing. The purpose of this community service activity is to socialize the use of Trecer using Microsoft Access in managing medical records Air Dingin Health Center, Padang City in 2019. Good medical record management is very helpful in carrying out activities so that they are not misplaced (missfile) and are not lost when the file is removed from the filing. The method used in this activity is training and socialization in the use of simple theoretical and practical applications. The result of this activity is that participants can use simple applications in managing medical records. Keywords: Medical records, public health center, tracer, microsoft access